Esthetic evaluation and patient‐centered outcomes in root‐coverage procedures. Issue 1 (4th March 2018) - Mounssif, Ilham; Stefanini, Martina; Mazzotti, Claudio; Marzadori, Matteo; Sangiorgi, Matteo; Zucchelli, Giovanni
Abstract: Treatment of buccal gingival recession is performed for esthetic concerns, root sensitivity, root caries and cervical abrasion resulting from incorrect toothbrushing. Over the years, clinicians and researchers have improved surgical techniques to achieve surrogate end points, such as complete root coverage, gingival recession reduction or keratinized tissue increase, ignoring the input from the patient regarding the true indications for treatment. In the past few years there has been an emphasis to include patient‐centered outcomes in the evaluation of root‐coverage procedures. The aim of this narrative review is to describe the professional objective assessment of the esthetic results after root‐coverage procedures and the patient perception of outcome in terms of esthetics, postoperative morbidity and dentinal hypersensitivity resolution after the treatment of gingival recessions. The need to align professional (surrogate) end points with patient‐centered outcomes (true end points) in the future is emphasized.